Performance monitoring of UPS battery using IoT - Vijaya Manasa, K; V Prabu, A; Sai Prathyusha, M; Varakumari, S (International Journal of Engineering and Technology, 2018)
The proposed proposal basically concentrate on energy efficient and cost effective model construct an automatic UPS monitoring and controlling system , with the context of PDA’s to machine level and machine level to PDA’s.RF is the essential information based communication system now a days i.e. Bluetooth/ZigBee/Wi-Fi . IoT based UPS provides the balancing tradeoff between monitoring and controlling the system remotely in order to increase the energy efficiency and production rate. Proposed system automatically monitor the 4 parameters ,i.e current ,voltage, temperature, power which runs on each UPS. During the drain out or worn-out if any of the pa-rameters like voltage andcurrent decreases from the ideal conditions then this will be monitored automatically and the values will be displayed on android app application and and uploaded to the cloud(IoT).The breakdown conditions of UPS will be notified to the chief engineer,supervisor and control room through SMS and IOT.